Adaptation of Convergence by Local Media Pikiran Rakyat and AyoBandung.com - Ridwan Saleh Fadillah; Aceng Abdullah; Abie Besman (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2022)
Convergence occurs because of the development of the internet, social media, and digital technology. In the realm of journalism, convergence refers to the practice of producing, distributing, and consuming content for multiple platforms in the form of text, photos, and videos by a single newsroom. The development of technology then gave birth to many disturbances and possibilities. Convergence challenges the media industry's already stable business model to adapt to changes. The purpose of this study is to discuss and compare how the adaptation and application of convergence that the local media